2016
DOI: 10.5693/djo.02.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Primary meningococcal conjunctivitis: an unusual case of transmission by saliva

Abstract: SummaryA 49-year-old diabetic man presented with a 2-day history of a painful right eye associated with a purulent discharge. Prior to becoming symptomatic, he reported that someone spat at him, resulting in direct contact between the saliva and his affected eye. Gram stain revealed numerous leucocytes with Gram-negative diplococci, and culture yielded Neisseria meningitidis (serogroup C). There was no evidence of any systemic infection, and blood cultures were negative for any growth. He was treated for prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
1
4
0
2
Order By: Relevance
“…Importantly, when detecting carriage of genogroupable meningococci, the method of testing culture-enriched saliva with a qPCR performed at least equally well compare with conventional diagnostic culture of oropharyngeal swab. Although numerous studies have implicated oral fluids in meningococcal transmission [8][9][10][11][12][13][14][15][16], very few actually tested saliva as specimen for assessing meningococcal carriage [18,19]. In this context, our findings are in line with a meningococcal carriage study conducted recently by Rodrigues et al [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, when detecting carriage of genogroupable meningococci, the method of testing culture-enriched saliva with a qPCR performed at least equally well compare with conventional diagnostic culture of oropharyngeal swab. Although numerous studies have implicated oral fluids in meningococcal transmission [8][9][10][11][12][13][14][15][16], very few actually tested saliva as specimen for assessing meningococcal carriage [18,19]. In this context, our findings are in line with a meningococcal carriage study conducted recently by Rodrigues et al [20].…”
Section: Discussionsupporting
confidence: 88%
“…Oropharyngeal samples have been widely used to detect meningococcal carriage as it has been reported that oropharyngeal samples are more sensitive than nasal or nasopharyngeal samples [7]. While a role for saliva in meningococcal transmission has been implicated in multiple studies [8][9][10][11][12][13][14][15][16], and closely-related Neisseria species are often cultured from saliva [17], few studies have tested saliva for meningococci [18][19][20][21]. In general, saliva is described to be poorly suited for meningococcal detection [19].…”
Section: Introductionmentioning
confidence: 99%
“…82 Both patients were given chemoprophylaxis, which is in line with the current recommendations for primary meningococcal conjunctivitis treatment. 82 However, as meningococcal carriage in pure saliva has previously been documented to be extremely low (0.4%), 81 transmission in these cases may have been via oropharyngeal secretions contained within the spit.…”
Section: Transmission Through Salivamentioning
confidence: 99%
“…Indeed, meningococcal ocular infections are most commonly associated with preceding SMD and rarely occur in isolation. Nonetheless, cases of primary meningococcal conjunctivitis (with no associated symptoms of SMD) resulting from close contact with another patient diagnosed with meningitis [101] and even through transmission from direct ocular contact with saliva from apparently healthy individuals [106,107], suggest that the routes of transmission to the eye may differ in each particular clinical case ( Table 1).…”
Section: Meningococcal Ophthalmiamentioning
confidence: 99%